2016
DOI: 10.1007/s12325-015-0279-0
|View full text |Cite
|
Sign up to set email alerts
|

Cost-Effectiveness of Ranibizumab Versus Aflibercept for Macular Edema Secondary to Branch Retinal Vein Occlusion: A UK Healthcare Perspective

Abstract: IntroductionRanibizumab and aflibercept are anti-vascular endothelial growth factor agents licensed for the treatment of visual impairment due to macular edema secondary to branch retinal vein occlusion (BRVO). The aim of this study was to estimate, from a UK healthcare payer’s perspective, the cost-effectiveness of ranibizumab versus aflibercept in this indication.MethodsA Markov model was used to simulate the outcomes and costs of treating BRVO. Patient baseline characteristics and efficacy data for ranibizu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
4
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…Based on meticulous analysis from the National Health Insurance Research Database, we are confident to demonstrate a higher risk of optic neuropathy among amiodarone-treated patients and suggest that physicians be alert to the new onset of visual disturbance in these patients. HUI-CHEN CHENG, MD 1,2 HUAN-JUI YEH, MD 3,4 NICOLE HUANG, PHD 5 AN-GUOR WANG, MD, PHD This study not only showed comparable letter gain with the BRAVO study 2 at 6 months, but also revealed the maintenance of this gain at 1 year. Although this confirms aflibercept to be efficacious in macular edema owing to BRVO, its uniqueness, in terms of longer action, from other antievascular endothelial growth factor agents has not been completely explored.…”
mentioning
confidence: 80%
See 2 more Smart Citations
“…Based on meticulous analysis from the National Health Insurance Research Database, we are confident to demonstrate a higher risk of optic neuropathy among amiodarone-treated patients and suggest that physicians be alert to the new onset of visual disturbance in these patients. HUI-CHEN CHENG, MD 1,2 HUAN-JUI YEH, MD 3,4 NICOLE HUANG, PHD 5 AN-GUOR WANG, MD, PHD This study not only showed comparable letter gain with the BRAVO study 2 at 6 months, but also revealed the maintenance of this gain at 1 year. Although this confirms aflibercept to be efficacious in macular edema owing to BRVO, its uniqueness, in terms of longer action, from other antievascular endothelial growth factor agents has not been completely explored.…”
mentioning
confidence: 80%
“…3,4 In many cases, the results from multivariable regression and propensity score analysis are similar. 5 Moreover, both statistical methods have their own limitations and none of them solve the problem of unknown confounders. 2 The instrumental variable approach may be a better option, because it may help to adjust for unobserved confounders.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…4,5,6 The release of inflammatory mediators like TNFalpha, leukotrienes, integrins, prostaglandins, and vascular endothelial growth factor (VEGF) follows endothelial damage in the affected blood vessels, resulting in an inflammatory response. 7 As proved, VEGF has a crucial role in the persistence and development of secondary M E. 8 This condition may lead to severe vision loss owing to possible complications including vitreous bleeding, retinal neovascularization, and macular ischemia, but the most frequent cause of diminution of vision is M E. 9 For many years, the first line of treatment for this M E was grid laser photocoagulation. With the presence of anti-VEGF agents, intravitreal injections of Ranibizumab and Aflibercept have become the first-line therapy methods for M E. As reported in the VIBRANT study, the use of anti-VEGF contributed to a large improvement in visual acuity and a decrease in CM T in eyes with M E secondary to BRVO.…”
Section: Introductionmentioning
confidence: 99%